2015
DOI: 10.1186/s13002-015-0046-y
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants sold in the markets of Antananarivo, Madagascar

Abstract: BackgroundThis study focuses on the large outdoor markets of the capital of Madagascar, Antananarivo. As the largest metropolitan area in Madagascar with a population of nearly two million, the region has great capacity for consumption of medicinal plant remedies despite numerous pharmacies. Medicinal plant use spans all socioeconomic levels, and the diverse metropolitan population allows us to study a wide variety of people who consume these plants for medical purposes. The purpose of this study is to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(40 citation statements)
references
References 16 publications
(19 reference statements)
2
33
1
4
Order By: Relevance
“…Babies’ fontanel problem are part of frequent diseases mentioned in this study and by Gallé et al [15] in their work in the southern Madagascar but not much found in other studies [24, 36, 43, 44]. These diseases are mainly caused by acute dehydration [47], which occurs frequently in the southern Madagascar.…”
Section: Discussionmentioning
confidence: 41%
“…Babies’ fontanel problem are part of frequent diseases mentioned in this study and by Gallé et al [15] in their work in the southern Madagascar but not much found in other studies [24, 36, 43, 44]. These diseases are mainly caused by acute dehydration [47], which occurs frequently in the southern Madagascar.…”
Section: Discussionmentioning
confidence: 41%
“…In addition, We were compared similiar species with different uses. For example, Crocus sativus is used as a tonic for heart and culinary use; Elaeagnus angustifolia is used as anti-diarrheal, treatment of gastric pain and hepatoprotective; Peganum harmala is used as antiseptic for air, treatment of scorpion bite, snake bite, toothache and soporific; Pimpinella anisum is used as carminative and culinary use; Rosa canina is used for Indigestion; Viscum album is used as treatment of body pain, knew joint pain, and abscess in Ilam, while Crocus sativus is used as vitamin-endorphins; Elaeagnus angustifolia is used as threatment of prostate, Peganum harmala is used as diuretic, relieve of kidney and bladder pain, Pimpinella anisum is used as treatment of stomach discomfort; Rosa canina is used as treatment of immunity diseases for finally, Viscum album is used as sedative effect and treatment of hormonal related diseases in Mersin-Adana [26].…”
Section: Discussionmentioning
confidence: 99%
“…Helichrysum flagellare for stomach ailments (Rakotoarivelo et al 2015) and scabies (Razafindraibe et al 2013). Herlichrysum faradifani serves to treat gonorrhea, cough, asthenia, fever, hepatitis, and stomach ulcers (Randriamiharisoa et al 2015) and Helichrysum gymnocephalum is used for stomach ulcers, wounds, headaches, and cough (Randriamiharisoa et al 2015;Randrianarivony et al 2017) (Figs. 4 and 5).…”
Section: Local Medicinal Usesmentioning
confidence: 99%